Nutrients and sea surface temperature drive harmful algal blooms in China’s coastal waters over the past decades - Wenyu Wei; Yue Han; Yuntao Zhou (Environmental Research Letters, 2023)
Eutrophication under climate change is well known to affect the community, productivity, and distribution of phytoplankton. However, the specific drivers of harmful algal blooms (HABs) in coastal China are not fully understood. Using HAB observed data since 1981, we quantified the distribution changes in HABs and estimated key environmental drivers (e.g. nutrients, sea surface temperature (SST), and precipitation) of HABs in China’s near seas. After 1981, the geographic range of HABs significantly expanded; moreover, the annual impacting period (AIP) of four of China’s near seas increased from 259% to 1090%. We found that rising total nitrogen (TN) or SST dominated the increase in the AIP in each near sea. Compared to the major contribution of TN to AIP in the other three near seas, TN has relatively weaker impacts than SST on AIP in the South China Sea (SCS). The peak of AIP in the SCS is highly correlated with extremely high SST. The significant contributions of climate change to HABs underscore the growing urgency to strictly control watershed nutrient input to mitigate marine eutrophication.